Medieval life - Langley, Andrew, 1949-; Brightling, Geoff; Dann, Geoff (New York : DK Publishing, 2011)
An illustrated look at various aspects of life in medieval Europe, covering everyday life, religion, royalty, and more.
The middle ages -- Medieval society -- A peasant's life -- Tied to the soil -- Running a manor -- A medieval home -- From kitchen to table -- Medieval women -- The great barons -- The royal court -- The medieval soldier -- The church -- Building a cathedral -- The art of decoration -- Holy orders -- Life in a monastery -- The written word -- Saints and pilgrims -- The Islamic world -- Trade and commerce -- Life in the town -- The guild masters -- The stonemasons -- Fairs and feast days -- Medieval music -- Plays and parades -- Death and disease -- The birth of a new age -- Did you know? -- Who's who? -- Find out more.
Includes bibliographical references (pages 69) and index.
Keywords: Civilization, Medieval -- Juvenile literature